Psycho-oncologists’ knowledge of cancer-related fatigue and the targets for improving education and training: results from a cross-sectional survey study - Milzer, Marlena; Wagner, Anna S.; Steindorf, Karen; Kiermeier, Senta; Schmidt, Martina; Maatouk, Imad (Supportive care in cancer, 2023)
Purpose: To explore psycho-oncologists’ knowledge of cancer-related fatigue and their self-efficacy to intervene for fatigue. We further aimed to examine the role of fatigue in psycho-oncological training and derive specific suggestions for improvements. Methods: For this cross-sectional survey study, psycho-oncologists working in Germany were systematically recruited via an address directory or invited by training institutes or colleagues. The online survey encompassed questions on knowledge of fatigue guidelines and interventions, self-efficacy, counseling, and fatigue in professional training. Data were analyzed descriptively and using Mann-Whitney U tests. A logistic regression analysis was performed to identify variables linked to fatigue guideline knowledge. Results: Seventy two percent of the 144 surveyed psycho-oncologists stated not knowing any fatigue-specific guidelines. Those unaware of guidelines reported a lower self-efficacy to intervene for fatigue. However, despite low knowledge of the guidelines, more than 80% of the participants felt well informed about fatigue and reported high self-efficacy. Most participants were aware of the empirical evidence for psychotherapeutic interventions (95%); everyday physical activity, e.g., taking a walk (98%); yoga (82%); and mindfulness-based interventions (82%). Knowledge gaps existed concerning the evidence of resistance/endurance training for treating fatigue. Knowing that resistance/endurance training is an effective treatment was related to an increased frequency to recommend it to patients. Suggestions to improve training for psycho-oncologists included raising awareness earlier in the career path and offering multidisciplinary trainings for fatigue. Conclusion: To improve fatigue-related guideline knowledge among psycho-oncologists and enhance implementation into clinical practice multidisciplinary trainings are needed. Psycho-oncologists should play an important role in fatigue management. Trial registration: Clinicaltrials.gov, identifier: NCT04921644. Registered in June 2021.
Veröffentlicht: 23. Juni 2023
Gesehen am 21.08.2023